Eco-Design of A Digital-Based Waste Bank in Sukoharjo: Pentahelix Synergy Approach - Karnawijaya, Ning; Rokhaniyah, Siti; Hadiningrum, Lila Pangestu (BISNIS, 2022)
Alternative solutions in overcoming the waste problem are carried out by developing a waste bank which is a social engineering activity that teaches people to sort waste and raises public awareness in waste management. The eco-design innovation of waste processing with a digital-based waste bank program with a synergistic pentahelix approach has become an innovation at the grassroots level, especially in Sukoharjo. This study uses a qualitative method, which is equipped with data analysis with descriptive statistics. The effectiveness of waste management is defined by the high amount of managed waste, the amount of waste being recycled, and the large economic benefits resulting from waste management. This is due to the low percentage of managed waste and the low percentage of recycled waste, which of course also has low economic benefits. Waste banks in the Sukoharjo area need to be further involved in this waste management, so that the effectiveness of its management increases and the economic benefits taken can be maximized. The existence of a waste bank has proven to be effective in reducing waste problems in Sukoharjo. it is necessary to use digital technology which is still rarely used by waste banks in Sukoharjo. Therefore, an eco-design of waste management through a digital-based Waste Bank in Sukoharjo needs to be implemented. Eco-design of waste management through the Waste Bank in this study is to use Pentahelix synergy, namely collaboration between elements of government, academia, the business sector, community, and the media.